2014
DOI: 10.4172/2155-983x.1000124
|View full text |Cite
|
Sign up to set email alerts
|

Miktoarm Star Micelles Containing Curcumin Reduce Cell Viability of Sensitized Glioblastoma

Abstract: Glioblastoma multiforme (GBM) is the most common and lethal primary intracranial tumor in humans. Monotherapeutic interventions have not been successful. The objective of the current studies was to establish the effective combination therapy consisting of pifitrin as a sensitizer, and curcumin as therapeutic incorporated into miktoarm micelles. A 2 B type miktoarm stars were prepared using a combination of click chemistry with ring opening polymerization on a core with orthogonal functionalities. These self-as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Polymeric carriers have the potential to improve the stability and solubility of curcumin [60][61][62]. Our research group has previously reported the incorporation of curcumin into A2B star polymer micelles and effectiveness of this preparation in glioblastoma [63,64]. A retention of curcumin's biological activity in nanocarriers, an enhanced permeability and retention (EPR) effect and diffusion of curcumin into the neighboring glioblastoma cells could provide an improved therapeutic intervention in vivo [65] Pyrrolidine-2 is an inhibitor of cPLA2a, a key rate limiting enzyme in the synthesis of eicosanoids and a necessary player in the formation of lipid droplets [66,67].…”
Section: Discussionmentioning
confidence: 99%
“…Polymeric carriers have the potential to improve the stability and solubility of curcumin [60][61][62]. Our research group has previously reported the incorporation of curcumin into A2B star polymer micelles and effectiveness of this preparation in glioblastoma [63,64]. A retention of curcumin's biological activity in nanocarriers, an enhanced permeability and retention (EPR) effect and diffusion of curcumin into the neighboring glioblastoma cells could provide an improved therapeutic intervention in vivo [65] Pyrrolidine-2 is an inhibitor of cPLA2a, a key rate limiting enzyme in the synthesis of eicosanoids and a necessary player in the formation of lipid droplets [66,67].…”
Section: Discussionmentioning
confidence: 99%
“…Owing to their tailorable architecture, superior CMCs, improved drug loading, and sustained drug release, there has been much recent interest in miktoarm star polymer-based assemblies for drug delivery [ 21 , 25 , 26 ]. Drug incorporation into micelles has been shown to have varied effects on the size of miktoarm micelles, where it can lower, increase, or have a negligible effect upon drug encapsulation [ 24 , 42 , 47 , 48 , 49 ]. Though generally, a decrease in size has been attributed to good polymer-drug compatibility [ 47 , 49 , 57 ].…”
Section: Amphiphilic Miktoarm Star Polymers: Self-assemblymentioning
confidence: 99%
“…Drug incorporation into micelles has been shown to have varied effects on the size of miktoarm micelles, where it can lower, increase, or have a negligible effect upon drug encapsulation [ 24 , 42 , 47 , 48 , 49 ]. Though generally, a decrease in size has been attributed to good polymer-drug compatibility [ 47 , 49 , 57 ]. One of the beneficial effects of including multiple branching arms as in miktoarm stars, is in increasing drug loading content into their self-assemblies.…”
Section: Amphiphilic Miktoarm Star Polymers: Self-assemblymentioning
confidence: 99%
“…As discussed earlier, multi-tasking is one of the key tenets of nanomedicine, and it requires nanocarriers to simultaneously perform multiple functions including drug loading and delivery, avoiding premature drug release, monitoring the fate of the drug as well as the carrier, and targeting the nanocarriers to intended site of action. In this regard, amphiphilic miktoarm star polymers are of specific interest to design synthetically articulated and tailor made micelles, and are currently being investigated extensively for the development of multifunctional nanocarriers for biological applications [117,118,119,120,121]. Miktoarm polymers have star shaped well-defined molecular architecture where different polymeric arms originate from a common central core.…”
Section: Dendrimers and Miktoarm Polymers: Interesting Platforms Fmentioning
confidence: 99%
“…Recently, we have used similar polymers for the encapsulation of curcumin to treat glioblastoma multiform tumor using combination therapy. Curcumin has poor aqueous solubility and low bioavailability [121]. Micellar encapsulation significantly improved the solubility of curcumin, and the combination of curcumin loaded micelles with pifitrin and temozolamide were quite effective in killing glioblastoma cells.…”
Section: Covalent Conjugation and Non-covalent Encapsulation In Dementioning
confidence: 99%